IMPLEMENTATION OF FULLY ONLINE MICROTEACHING MODEL TO IMPROVE THE TEACHING COMPETENCE OF ARABIC LANGUAGE PRE-SERVICE STUDENT TEACHERS - Hisbullah Huda; Umi Hanifah (ALSINATUNA, 2023)
Pandemic has changed microteaching models from offline to fully online. This requires skills that integrate technology into the lesson planning and teaching practice. This study aims to describe the implementation of fully online microteaching models to improve the teaching competence of Arabic language pre-service student teachers, its problems and solutions. This study uses qualitative descriptive method. Data were collected using observation, interviews, and documentation techniques and analyzed with Miles, Huberman, and Saldana interactive model of qualitative analysis technique. The study results show that the Arabic Microteaching course at the Faculty of Education and Teacher Training of Sunan Ampel Islamic State University was designed to be fully online using two models, namely synchronous and asynchronous models, using the media of Google Classroom and Google Meet. This model has its problems. The limited internet package made the students unable to turn on their cameras. This made the teaching practice less interactive. It also hampered the development of the social skills of the teaching practice students. The problem was overcome by regulating the turn to turn on the camera in the synchronous model and maximizing the offline asynchronous model by getting the students to attend [the class] and by recording the teaching practice in video. In this way, the fully online microteaching model can make Arabic language pre-service student teachers more competent in designing their lesson plans and in practicing digital-based learning creatively and innovatively.